The Impact of Government Accounting Standards Implementation, Internal Control Systems, and Human Resource Competence on Regional Financial Report Quality - Yenni, Elfita; Junaedi, Achmad Tavip; Wijaya, Evelyn (Journal of Applied Business and Technology, 2024)
This study introduces a comprehensive model that simultaneously investigates the interplay of Government Accounting Standards Implementation, Internal Control Systems, and Human Resource Competence in determining regional financial report quality. This study employs a quantitative research design. The sample size for this study is 96 respondents, meeting the minimum requirement for Structural Equation Modeling (SEM) analysis. Only human resource competence can improve regional financial report quality. These findings align with Agency Theory, emphasizing that competent agents (human resources) are critical for reducing information asymmetry and improving financial reporting. They also connect to Institutional Theory, illustrating that formal systems like GAS and ICS require human agency to operationalize institutional norms effectively. Finally, the results support Resource-Based Theory (RBT), highlighting HRC as a strategic resource that drives organizational success in financial reporting. Future studies should explore the impact of external audits, political stability, and organizational culture on financial report quality.